Success factors for music-based crowdfunding in the Finnish context - Chinakaeva, Giulnara (2019)
This thesis paper builds on the knowledge that vast majority of crowdfunding campaigns fail to reach their fundraising goals. Hence, current research intends to determine a variety of factors influencing the success of crowdfunding projects. The study is particularly interested in music-based crowdfunding initiatives in the Finnish context. The specific research question is as follows: what factors are associated with the success of music-based crowdfunding campaigns in Finland? Current research is an empirical study which follows a quantitative research tradition and applies logistic regression analysis of data. Empirical data was collected from the leading Finnish reward-based crowdfunding platform Mesenaatti.me. Research findings indicate that such factors as number of mentions on Facebook and number of reward types are associated with the success of crowdfunding campaigns.